The Efficacy of Semi-Rigid Ureteroscopy in the Treatment of Lower Ureteric Stone in Al-Muthanna Province - Hussein Ali Al-Hamdani (American Journal of Biomedicine and Pharmacy, 2026)
Objective: The efficacy of semi-rigid ureteroscopy in the treatment of lower ureteric stone in Al-Muthanna province. Patients and methods: This study was conducted at Al-Hussein Teaching Hospital from 22 December 2021 to 10 April 2022. Twenty-seven patients (16 females, 11 males) aged between 11 and 65 years (mean 38 years, with lower ureter stones from 4 mm to 19 mm (mean 11.5 mm), underwent treatment for lower ureteral stones with semi-rigid ureteroscopy and were included in this study. Results: Success rate was 85%. There were no major perioperative complications; minor complications were encountered in a few patients and treated accordingly. Conclusion: S-URS is an efficient and safe treatment for lower ureteral stones, with an increased efficiency with smaller stones less than 1 cm in size. Morbidity, hospital stay, and complication rates are low, with a good stone-free rate.